HCI and Affective Health: Taking stock of a decade of studies and charting future research directions - Sanches, Pedro; Janson, Axel; Karpashevich, Pavel; Nadal, Camille; Qu, Chengcheng; Daudén Roquet, Claudia; Umair, Muhammad; Windlin, Charles; Doherty, Gavin; Höök, Kristina; Sas, Corina (ACM, 2019)
In the last decade, the number of articles on HCI and health has increased dramatically. We extracted 139 papers on depression, anxiety and bipolar health issues from 10 years of SIGCHI conference proceedings. 72 of these were published in the last two years. A systematic analysis of this growing body of literature revealed that most innovation happens in automated diagnosis, and self-tracking, although there are innovative ideas in tangible interfaces. We noted an overemphasis on data production without consideration of how it leads to fruitful interventions. Moreover, we see a need to promote ethical practices for involvement of people living with affective disorders. Finally, although only 16 studies evaluate technologies in a clinical context, several forms of support and intervention illustrate how rich insights are gained from evaluations with real patients. Our findings highlight potential for growth in the design space of affective health technologies.
Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems
PUBLISHED
Keywords: Affective disorders; Literature review; Innovation; Clinical trials; Ethical issues; AFFECTIVE DISORDER; Health informatics; MENTAL HEALTH